Clinical Usefulness, Safety, and Plasma Concentration of Ropivacaine 0.5% for Inguinal Hernia Repair in Regional Anesthesia. Issue 4 (1st July 2001) - Wulf, Hinnerk; Behnke, Hagen; Vogel, Ilka; Schröder, Jörg
Abstract : Background and Objective: The aim of this study was to evaluate the pharmacokinetics, feasibility, and clinical effects of ropivacaine in regional anesthesia (ilioinguinal-iliohypogastric blocks [IIB], genitofemoral block plus local infiltration) for inguinal hernia repair. Methods: Following ethics committee approval and informed consent, 21 male adults received 60 mL ropivacaine 0.5% (without vasoconstrictor). In 11 patients, further injections of 5 to 10 mL were given while preparing the hernial sack. Plasma concentration of ropivacaine was determined in venous blood after 10, 20, 30, 45, 60, 90, 120, and 300 minutes using reversed-phase high pressure liquid chromatography (HPLC). Results: Peak plasma concentrations of ropivacaine were 1.5 ± 0.6 (0.7 to 2.6) μ g/mL (mean ± SD [range]). These maximum concentrations occurred after 45 (30 to 60) minutes (median [range]). No signs of central nervous or cardiovascular toxicity were observed. Twelve of 21 patients did not need any additional analgesics within 24 hours postoperatively. One patient had a femoral motor block lasting 6 hours, 5 patients reported sensory femoral block lasting 5 to 12 hours. Patients, as well as the surgeon, were very satisfied with the procedure, and all patients stated that they would like to have it performed again that way in case of an inguinal hernia on the opposite side. Conclusion: A ropivacaine dose of 60 to 70 mL of 0.5% appears adequate for regional anesthesia for inguinal hernia repair regarding conditions for surgery, safety, ambulation, and postoperative pain relief.